PESAN POLITIK MEGAWATI SOEKARNOPUTRI DALAM PIDATO ULANG TAHUN KE-44 PDI PERJUANGAN - Ali Kusno (Kelasa, 2017)
AbstractChairman of the Partai Demokrasi Indonesia Perjuangan (PDIP) Megawati delivered a politicalspeech in the 44th anniversary of PDIP, Megawati's speech reaped a variety of criticisms fromsome parties without intrepreting the whole content of the speech thoroughly. This study aims toanalyze the political messages contained in the discourse of Megawat’s political speech. This studyuses a model of critical discourse analysis by Fairclough. The data are taken from the discourse ofMegawati's speech. The data are analyzed using an interactive model. The results show thatMegawati’s political speech does not harm certain parties. The message delivered is a purepersuasion to the country to uphold Pancasila, the 1945 Constitution, and to maintain the nationalunity which is knows as Bhineka Tunggal Ika. Even if there is an apposing party, it could bepossible because of differences in political views and interests. The issue often arises when peoplein the political parties are sometimes too reactive to the statement and associate it with racialissues. The problems that actually have nothing to do with the racial issues can be a big issuebecause they were exaggerated. AbstrakKetua Umum Partai Demokrasi Indonesia Perjuangan (PDIP) Megawati menyampaikan pidatopolitik dalam HUT ke-44 PDIP. Pidato Megawati itu menuai beragam kecaman dari beberapa pihaktanpa memaknainya secara menyeluruh. Penelitian ini bertujuan menganalisis pesan politik yangterdapat dalam pidato Megawati tersebut. Penelitian ini menggunakan analisis wacana kritisModel Fairclough. Data penelitian diambil dari wacana pidato Megawati tersebut. Teknik analisisdata menggunakan model interaktif. Hasil penelitian menunjukkan bahwa Megawati dalam pidatopolitiknya tidak ada satu pernyataan pun yang mencederai pihak tertentu. Hal yang disampaikanmurni persuasi terhadap bangsa Indonesia untuk menjunjung pancasila, UUD 1945, dan menjagapersatuan bangsa yang Berbhineka Tunggal Ika. Kalaupun ada pihak lain menentang, bisadimungkinkan karena perbedaan pandangan politik dan kepentingan. Persoalan justru seringmuncul ketika tokoh-tokoh tersebut reaktif terhadap pernyataan dan mengaitkannya dengan isuSARA. Permasalahan yang sebenarnya tidak ada kaitannya (SARA) dapat menjadi isu besar karenadibesar-besarkan.